Village-Owned Enterprise Governance in the Perspective of Reinventing Local Government - Dian Pratama; Eny Haryati; Dian Ferriswara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze: Governance of BUMDes based on reinventing local government. This study uses a qualitative approach with a multiple case study design. This research was conducted in three locations with BUMDes that have different levels of performance: BUMDes Tirta Mandiri (Ponggok Village, Klaten, Central Java): For example, BUMDes are successful. Sumber Rejeki BUMDes (Sumberagung Village, Jember, East Java): As an example of BUMDes with medium performance. BUMDes Tani Makmur (Sukorejo Village, Malang Regency, East Java): As an example of BUMDes that are still developing. The data obtained were analyzed qualitatively using the thematic analysis method. The stages of data analysis are as follows: (1) Data Collection (2) Transcription and Coding: (3) Thematic Analysis: (4) Data Triangulation. The results of the study show that BUMDes Governance based on local government reinventing includes Community Participation: Encouraging active community involvement in the decision-making process. Community participation in the management of BUMDes refers to four participations, namely (1) participation in planning, (2) participation in program implementation, (3) participation in assessment and evaluation, and (4) participation in the utilization of results. Transparency in governance refers to openness in providing information related to the management of BUMDes to the public. Document accessibility available, Complete and clear information, Open management processes, Regulatory framework that ensures transparency, Information written and communicated to stakeholders. Accountability in governance refers to legal accountability, process accountability, program accountability. BUMDesa innovation as a new idea aims to initiate, improve and improve community entrepreneurship. Innovation in products and services. Innovation in BUMDes includes the creation of new products, improving the quality of existing products, and developing services that are relevant to the needs of the community and the market. Service innovation includes improving ways of providing services that are faster, more convenient, or more in line with customer needs.